tert-Butyl N-(4-methyl-2-pyridyl)carbamate - Koch, Pierre (International Union of Crystallography, 2008)
The crystal structure of the title compound, C(11)H(16)N(2)O(2), contains two crystallographically independent molecules forming dimers by pairs of intermolecular N—H⋯N hydrogen bonds. The two molecules are related by a pseudo-twofold axis. The dihedral angle between the pyridine ring and the carbamate plane differs in the two molecules [12.1 (3) and 3.5 (3)°].